FORMULASI GEL ANTIOKSIDAN DARI EKSTRAK ETANOL BUNGA BROKOLI (Brassica oleracea L. var. italica) DENGAN MENGGUNAKAN METHOCEL K15M PREMIUM EP - Eka Puspita; Teuku Nanda Saifullah Sulaeman; Dhadhang Wahyu Kurniawan (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2012)
ABSTRACT Broccoli is one kind of plant variety compounds antioxidant unit that inhibited potentially damaging of body’s tissues and organ cause of over amount of free radical accumulation. New research in USA indicated that broccoli can help skin cell against the damaging effect caused of UV light radiation. This research used laboratorium experimental design, scoring technique and quantitative descriptive analysis. The purpose of this research is to explored that broccoli ethanol extract (Brasicca oleracea var Italica) could be formulated as an antioxidant gel by Metocel K15M Premium EP base, produced a good physical characteristic and still has an antioxidant activity. This research is done by extraction, extract characterisation, gel formulation by four variation of extract and evaluated the formulation of gel. Extraction is done by maseration with ethanol 70%, characterisation is done by organoleptic observation envelope in colour, smell, taste and form of extract. Gel formulation is made by four formulas of gel which is added by an ethanol extract of broccoli with different concentration. Evaluated gel is done by physical stability test and antioxidant activity test with DPPH methods. The result of this research indicated that gel formulation produced formula 1, formula 2, formula 3 and formula 4. The most optimal gel formulation was formula 2 which is detemined from physical stability aspect based on changes in physical appearance, colour, odor, pH and viscosity during 28 days storage periods. Antioxidant activity is determined by DPPH (1,1-Diphenyl-2-Picryl Hidrazyl) testing method. This test showed that IC50 of broccoli (Brasicca oleracea var Italica) ethanol extract is 12,479 mg/mL. Key words: Gel formulation, antioxidant, broccoli ethanol extract, Methocel K15M Premium EP.